Management of human resources and quality of service in the Superintendencia Nacional de Migraciones, Headquarters of Lima, 2019 - Quispe LLanos, Renan (2020)
The objective of this article is to determine how human resources management influences the quality of service to the users of the Superintendencia Nacional de Migraciones, Headquarters of Lima – Peru, 2019. The study is descriptive and non-experimental cross-sectional design which was directed to a sample of 168 collaborators and 381 users. Among the obtained results, it has been determined that 34% of the employees surveyed almost never feel motivated by the work done and the 60% of the surveyed users consider that the treatment of the server is only sometimes adequate. It put forwards as value proposal an outline on personnel management processes and the bases for empowerment in decision making. There is a very significant relationship between the organizational climate, recognition of personnel, the commitment of collaborators; and the quality of service to the user for having found a p-value of 0.000 <α = 0.05 through the Rho Spearman correlation.